(untitled) (Research, Society and Development, 2020)
This study aimed to identify the predisposition to the occurrence of adverse events in intensive care units. This is a descriptive research with a quantitative, cross-sectional survey approach. The study was carried out in the Intensive Care Center of a reference hospital in the state of Ceará. The study population was composed of nurses who worked in the care of the three adult ICUs. Data collection was performed through an instrument that assesses the unit’s predisposition to adverse events through the perception of nurses. The Structure domain obtained an average perception of aspects that may predispose to the occurrence of adverse events. The Process domain, on the other hand, obtained a low perception of aspects that may predispose to the occurrence of adverse events. It is expected that in both domains they obtain a low perception of aspects that may predispose to the occurrence of adverse events. Care is compromised in relation to the Structure domain, highlighting some specific weaknesses, for example the continued training of the nursing team, which must be strengthened, as well as it is necessary for the continuing education committee to be present in the care environment, especially in the ICU. Regarding the process aspects present in care, in general, nurses showed a low perception of the presence of such aspects that could predispose to the occurrence of adverse events. In this way, aspects of the process should be strengthened.